A D, D‐carboxypeptidase is required for Vibrio cholerae halotolerance. (February 2015) - Möll, Andrea; Dörr, Tobias; Alvarez, Laura; Davis, Brigid M.; Cava, Felipe; Waldor, Matthew K.
Summary The biological roles of low molecular weight penicillin‐binding proteins (LMW PBP) have been difficult to discern in Gram‐negative organisms. In Escherichia coli, mutants lacking these proteins often have no phenotype, and cells lacking all seven LMW PBPs remain viable. In contrast, we report here that Vibrio cholerae lacking DacA‐1, a PBP5 homologue, displays slow growth, aberrant morphology and altered peptidoglycan (PG) homeostasis in Luria–Bertani (LB) medium, as well as a profound plating defect. DacA‐1 alone among V. cholerae's LMW PBPs is critical for bacterial growth; mutants lacking the related protein DacA‐2 and/or homologues of PBP4 or PBP7 displayed normal growth and morphology. Remarkably, the growth and morphology of the dacA‐1 mutant were unimpaired in LB media containing reduced concentrations of NaCl (100 mM or less), and also within suckling mice, a model host for the study of cholera pathogenesis. Peptidoglycan from the dacA‐1 mutant contained elevated pentapeptide levels in standard and low salt media, and comparative analyses suggest that DacA‐1 is V. cholerae's principal DD‐carboxypeptidase. The basis for the dacA‐1 mutant's halosensitivity is unknown; nonetheless, the mutant's survival in biochemically uncharacterized environments (such as the suckling mouse intestine) can be used as a reporter of low Na+ content.